substituted it to

dv = e^(x) dx

v = e^(x)

u = (cos(x))

u = -sin(x) dx

and this one goes infinity for me

help needed for what to sub ... i dunno how the integrator got a short answer

Printable View

- Jul 11th 2007, 06:33 AM^_^Engineer_Adam^_^integration: by parts

substituted it to

dv = e^(x) dx

v = e^(x)

u = (cos(x))

u = -sin(x) dx

and this one goes infinity for me

help needed for what to sub ... i dunno how the integrator got a short answer - Jul 11th 2007, 06:47 AMThePerfectHacker
- Jul 11th 2007, 07:06 AM^_^Engineer_Adam^_^
thanks alot :D